2019
DOI: 10.1111/jfpp.14016
|View full text |Cite
|
Sign up to set email alerts
|

Frankfurters formulated with pecan nut paste and oregano essential oil as functional components: Proximate composition, lipid oxidation, and fatty acid profile

Abstract: This study aimed to evaluate the quality of frankfurter sausages containing pecan nut paste (PN) and Mexican oregano essential oil (MO) of two varieties (Poliomintha longiflora Gray, MOP; and Lippia berlandieri, MOL). Frankfurters were processed under six treatments: control, MOP (control + 100 ppm MOP), MOL (control + 100 ppm MOL), MOP–N (MOP treatment + 6% PN), MOL–N (MOL treatment + 6% PN), and C–N (control + 6% PN). PN and MO did not influence (p > 0.05) the proximate composition of sausages; lipid oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 67 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…In previous work we showed that the partial replacement of fat with pecan nut paste added to oregano oil does not change the proximate composition of frankfurters [ 5 ]. The average values for moisture, protein, fat, and ash content of sausages of all the treatments are 69.39%, 14.89%, 8.17%, and 3.71%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous work we showed that the partial replacement of fat with pecan nut paste added to oregano oil does not change the proximate composition of frankfurters [ 5 ]. The average values for moisture, protein, fat, and ash content of sausages of all the treatments are 69.39%, 14.89%, 8.17%, and 3.71%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the low acceptability could rely on the oregano oil compounds. The highest amount of volatiles components present in oregano are carvacrol and thymol [ 5 ]. However, Al-Hijazeen et al [ 25 ] observed that a 200 ppm oregano oil combined with 10 ppm of tannic acid presented high score on the overall acceptability of the cooked chicken meats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations